2006
DOI: 10.1007/s10815-006-9036-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low-Dose Human Chorionic Gonadotropin (hCG) in a GnRH Antagonist Protocol

Abstract: Purpose:To examine the efficacy of low-dose hCG using a GnRH antagonist protocol. Methods: Prospective randomized study was performed at the Kyono Ladies Clinic. One hundred ninety-two women (<40 -years old, <3 previous cycles) were randomly assigned to GnRH agonist (buserelin) long protocol (LP, n = 66), GnRH antagonist (cetrorelix) with no low-dose hCG protocol (NhCGP, n = 63), or GnRH antagonist with low-dose hCG protocol (hCGP, n = 63). Results: The hCGP was associated with reduced total amounts of FSH, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…The administration of hCG promotes follicular growth and oocyte maturation, thereby decreasing the amount of FSH needed for ovarian stimulation (12,14,15). We previously published a study that showed that hCG supplementation results in lower medication costs and similar pregnancy rates compared with FSH-only stimulation for GnRH-antagonist IVF cycles (14).…”
mentioning
confidence: 99%
“…The administration of hCG promotes follicular growth and oocyte maturation, thereby decreasing the amount of FSH needed for ovarian stimulation (12,14,15). We previously published a study that showed that hCG supplementation results in lower medication costs and similar pregnancy rates compared with FSH-only stimulation for GnRH-antagonist IVF cycles (14).…”
mentioning
confidence: 99%
“…A study by Filicori et al further demonstrated a significantly higher fertilization rate in patients receiving hCG versus rFSH only (74% versus 48%) (104). The remainder of the trials did not show any differences in outcomes with hCG with regards to fertilization, implantation, or pregnancy (105)(106)(107)109). These RCT total 614 patients and demonstrate that the addition of hCG results in higher estradiol levels and at least comparable ART outcomes to rFSH stimulation only.…”
Section: Human Chorionic Gonadotropinmentioning
confidence: 90%
“…All trials were initiated with rFSH only for stimulation with hCG added when the follicles were between 12-14mm in size. Five of the trials reported a significantly higher estradiol level on the day of hCG in patients randomized to receive hCG stimulation, with increases in estradiol ranging from 700-1500 pg/ml (104)(105)(106)(107)109). A study by Filicori et al further demonstrated a significantly higher fertilization rate in patients receiving hCG versus rFSH only (74% versus 48%) (104).…”
Section: Human Chorionic Gonadotropinmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several other studies have shown better outcomes with additional LH in poor responders when GnRH-a short or long protocols were applied [40][41][42] whereas in the study of Bjercke et al and Hompes et al [43,44] in normal responders, the clinical outcomes were similar between rFSH and hMG groups. Some other trials demonstrated favorable treatment outcomes in an antagonist protocol in patients who received low dose hCG [18,45].…”
Section: Variablementioning
confidence: 99%